2021
DOI: 10.3390/agronomy11122481
|View full text |Cite
|
Sign up to set email alerts
|

Can Seaweed Extract Improve Yield and Quality of Brewing Barley Subjected to Different Levels of Nitrogen Fertilization?

Abstract: Barley is the primary matrix for malting process of beer production. Farmers count on increasing cultivation inputs, especially nitrogen fertilization, in order to reach a higher yield. Nevertheless, an overuse of nitrogen, besides causing environmental damages, can determine a deterioration of quality traits of malting barley, in particular an increase in grains protein content, which should range between 10 and 11% as required by the mating industry. Over two successive years, barley was grown under 4 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
3
2
0
Order By: Relevance
“…The reason for this may be due to stimulating the formation of new spikes of seedlings by seaweed extract where it can be stimulating the formation of new spikes of seedlings (side tillers) of the plant, which increases the total number of spikes. These results are consistent with what was found by [32,33,34] The results of Table (6) showed that there was a significant difference among the levels of the Optimus-plus (bio-fertilizer) in terms of the number of spikes, as it reached (428.06 spikes.m -2 ) at the level of (150 ml.100 L of water -1 ), the reason for the increase in the number of spikes is that the amino acids present in the bio-fertilizer and the organic materials contributed to an increase in cell expansion, which ultimately led to an increase in the spikes number. This result is in line with what was reported by [35,36].…”
Section: Spikes No (Spikes M -2 )supporting
confidence: 94%
See 1 more Smart Citation
“…The reason for this may be due to stimulating the formation of new spikes of seedlings by seaweed extract where it can be stimulating the formation of new spikes of seedlings (side tillers) of the plant, which increases the total number of spikes. These results are consistent with what was found by [32,33,34] The results of Table (6) showed that there was a significant difference among the levels of the Optimus-plus (bio-fertilizer) in terms of the number of spikes, as it reached (428.06 spikes.m -2 ) at the level of (150 ml.100 L of water -1 ), the reason for the increase in the number of spikes is that the amino acids present in the bio-fertilizer and the organic materials contributed to an increase in cell expansion, which ultimately led to an increase in the spikes number. This result is in line with what was reported by [35,36].…”
Section: Spikes No (Spikes M -2 )supporting
confidence: 94%
“…The reason for the increase in the harvest index may be attributed to the fact that increasing the number of ears per unit area of bio-fertilizers may lead to an increase in the number of spikes per unit of cultivated area, which increases the expected crop quantity by a percentage larger and increases the value of the harvest index. This result agreed with what was reported by [32,37]. Table (8) also showed interaction between the seaweed extract and the bio-fertilizer had a significant effect on the harvest index trait, as the treatment (300 ml.100 L of water -1 (Algareen-twin), and 150 ml.100 L of water -1 (Optimus-plus)) which reached to (57.05%).…”
Section: Harvest Index (Hi)supporting
confidence: 91%
“…Cucumber plants treated by 1200 mg/L seaweed extracts in most cases outperformed control and other treated plants in terms of plant height, leaf area, root length, shoot DW and root DW. The present results are in agreement with those who recorded that the low concentrations of seaweed extracts promoted the seedling growth [1][2][3][4][5][6][7][8][12][13].…”
Section: Chemical Composition Of Seaweed Extractssupporting
confidence: 93%
“…Seaweed extracts are used in agriculture as biostimulants as a low concentration is required to induce a positive response in plant growth and increase plant tolerance to various stress factors [4]. The beneficial effects of seaweed extracts on plant growth can be attributed to direct and indirect stimulation mechanisms [5]. Seaweed extracts are able not only to improve crop growth, but also to increase nutrient uptake, photosynthesis, yield, quality and plant tolerance to abiotic and biotic stress [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Among them seaweeds are considered as valuable source of unique polysaccharide elissitors and perspective biostimulants, which are not found in terrestrial plants [1]. Seaweeds contain a wide spectrum of biologically active substances, oils, lipids, fatty acids, microelements, vitamins, pigments and hormones due to they exhibit positive effect on the plant growth, development and yield [2][3][4][5][6]; activate the formation of different metabolites, particularly, phenolic compounds playing one of the cue role in plant defense, and, therefore, increase plant resistance to various stress factors, including abiotic stress and diseases caused by viral, fungal, bacterial infections and plant pests [1,4,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%